Detection of coronary stenosis at rest using BOLD-CMR - Arnold, J; Jerosch-Herold, M; Karamitsos, T; Francis, J; Bhamra-Ariza, P; Sarwar, R; Choudhury, R; Selvanayagam, J; Neubauer, S (Elsevier, 2016)
In the clinical evaluation of coronary artery disease (CAD), a desirable goal is to identify functionally significant disease without recourse to physical or pharmacological stress. Previous studies using myocardial contrast echocardiography have demonstrated microvascular dilation at rest in post-stenotic myocardium (1). Blood oxygen level–dependent (BOLD) cardiac magnetic resonance is a technique that can detect myocardial ischemia (2). The transition from diamagnetic oxyhemoglobin to paramagnetic deoxyhemoglobin induces T2 or T2* differences, thereby generating oxygen-dependent magnetic resonance contrast. In diseased myocardium, BOLD signal differences relative to normal myocardium may reflect not only differences of blood oxygenation, but also of vascular volume. Increased microvascular volume, with concomitant increase in the absolute quantity of hemoglobin, is expected to alter BOLD signal. We postulated that BOLD imaging at rest could be exploited to detect functionally significant CAD without stress.